ВОЗМОЖНОСТИ РЕНТГЕНОВСКОЙ МАММОГРАФИИ "МАЛЫХ" ФОРМ РАКА МОЛОЧНОЙ ЖЕЛЕЗЫ НА ФОНЕ ФИБРОЗНО-КИСТОЗНОЙ БОЛЕЗНИ - D. G. Bukharin; S. A. Velichko; I. G. Frolova (Бюллетень сибирской медицины, 2014)
The analysis of radiologic signs of small size breast cancer in patients with fibrocystic disease has been carried out.The conventional approach to the analysis of mammograms of these patients based on the detection of primary, secondary and indirect cancer symptoms has been found to have insufficient effect.The relationship between mammographic findings and primary tumor size, character and concomitant disease intensity has been proved.The data obtained allow us to arrange the diagnostic process and management of patients with breast lesions.